Answer:
The answer is=-3m-4n+14
Explanation:
Step-by-step explanation:
Step 1: Express terms in the form R-S+T
Where R=11-2m, S=n+5, T=-m-3n+8
Replace values for R, S and T in R-S+T= (11-2m)-(n+5)+(-m-3n+8)
Step 1: Collect all the like terms
Open the brackets
11-2m-n-5-m-3n+8
Like terms are similar variables, for example;
(-2m, -m) are all like terms since they have a common variable (m)
(-n, -3n) are also like terms since they have a common variable (n)
(11,-5,8) are constants
Step 2: Solve
-2m-m-n-3n+11+8-5=-3m-4n+14
The answer is -3m-4n+14